China in Foreign Media: Assessing China’s Image in Online Editions of Nigeria’s Leading Newspapers in 2017 - Anunne, Uchenna Kingsley; Yan, Lifeng (European Scientific Journal, ESJ, 2018)
China has witnessed huge economic growth in recent decades. The growth has come with its own challenges, namely the desire for more resources to not only sustain the growth but to attain greater heights. Many media houses abroad have faulted China’s approach towards meeting these demands. To many media houses, China is bullying its neighbors in pursuit of water and associated mineral resources. Its diplomatic and economic maneuvers in Africa have also attracted criticism from a section of international media who see the move as neo-colonialism and an attempt to entrap African countries with irredeemable debts. Most of the criticisms have come from western media that have heavy influence on Nigerian media. With its debt profile to China estimated at USD 10billion and Chinese firms handling multi-million dollar projects, Nigeria is one of the African countries where China’s presence has come under scrutiny. Using quantitative research method and content analysis of 420 editorial materials, this study assess the image portrayal of China in the online editions of Nigeria’s leading newspapers in 2017. But, did the studied newspapers see China as a positive force in Nigeria’s economic, social and political firmament or represent China negatively? Our findings show that Nigeria newspapers perceive China as a force for good.